A Deixis Analysis of Song Lyrics in Back To You by Selena Gomes - Arini Hidayah (Faculty of Language and Literature, University of Surakarta, 2019)
The objectives of this study are to identify the kinds of deixis that are used in the song lyrics Back To You, to find out the dominant types of deixis that are used in the song lyrics Back To You. This research belongs to qualitative research. The researcher uses observation method, while the data collection techniques is listening and analyzing the songs of “Back to you” by Selena Gomez. The result of this research is the song lyrics of Back To You use all types of deixis. Person deixis almost occurs in every lyric of Back To You. There are 45 data of person deixis consisting of first, second and third person deixis. In addition, the other types such as time deixis (2 data) and place deixis (1 datum) also occur in a song of Back To You. Most of personal deixis in Back To You song lyric refer to the speaker itself which are encoded by first singular person deixis like I and My. While for first plural person deixis which are We mostly refer to the speaker.